A Histopathological Comparison of Pulpotomy with Sodium Hypochlorite and Formocresol - Haghgoo, Roza; Abbasi, Farid (Iranian Endodontic Journal, 2012)
Introduction: Formocresol is widely used in primary teeth pulpotomies; however it is known to have several side effects. The purpose of this study was to assess pulpal changes of primary teeth pulps after pulpotomy with sodium hypochlorite and formocresol. Materials and Methods: In this randomized clinical trial, 22 teeth were selected. These teeth were randomly divided into 2 groups (formocresol; n=11 and sodium hypochlorite n=11). Two months post-operatively teeth were extracted and pulpal responses were evaluated by recording the degree of inflammation and extent of pulpal involvement. Dentinal bridge formation was also evaluated. Finally the data was analyzed with McNemartest. Results: The formocresol group demonstrated mild inflammation in 4 cases whereas sodium hypochlorite had mild inflammation in six cases. Severe inflammation was only found in 1 case in the sodium hypochlorite group, but it was present in 4 cases in the formocresol group. In sodium hypochlorite group there were no cases of necrosis, and dentinal bridge was found in 3 cases, unlike, the formocresol group which had necrosis but no dentinal bridge formation. Conclusion: Based on the results of this study sodium hypochlorite may be a suitable solution for conducting pulpotomy in primary teeth.